Chronic haloperidol administration downregulates select BDNF transcript and protein levels in the dorsolateral prefrontal cortex of rhesus monkeys - Hemby, Scott E.; McIntosh, Scot (Frontiers in Psychiatry, 2023)
Post-mortem studies in the prefrontal cortex and hippocampal formation from schizophrenia patients have revealed significant disruptions in the expression molecules associated with cytoarchitecture, synaptic structure, function, and plasticity, known to be regulated in part by brain derived neurotrophic factor (BDNF). Interestingly, several studies using postmortem brain tissue from individuals diagnosed with schizophrenia have revealed a significant reduction in BDNF mRNA and protein levels in the dorsolateral prefrontal cortex (DLPFC), hippocampus and related areas; however, differentiating the effects of illness from antipsychotic history has remained difficult. We hypothesized that chronic antipsychotic treatment may contribute to the altered BDNF mRNA and protein expression observed in post-mortem brains of individuals diagnosed with schizophrenia. To address the influence of antipsychotic administration on BDNF expression in the primate brain, rhesus monkeys orally administered haloperidol, clozapine, or vehicle twice daily for 180 days. We found BDNF splice variants 4 and 5 in the DLPFC and variant 2 in the EC were significantly down-regulated following chronic administration of haloperidol. In addition, proBDNF and mature BDNF expression in the DLPFC, but not the EC, were significantly reduced. Based on the known regulation of BDNF expression by BDNF-AS, we assessed the expression of this lncRNA and found expression was significantly upregulated in the DLPFC, but not EC. The results of the present study provide evidence of haloperidol-induced regulation of BDNF mRNA and protein expression in the DLFPC and suggest an important role for BDNF-AS in this regulation. Given the role of BDNF in synaptic plasticity, neuronal survival and maintenance, aberrant expression induced by haloperidol likely has significant ramifications for neuronal populations and circuits in primate cortex.